A Foxtail-Shaped Vermilion Flap to Reconstruct the Medial Tubercle in Asymmetric Bilateral Cleft Lip With Contralateral Lesser Form Defect. (September 2019) - Nakajima, Yuta; Yuzuriha, Shunsuke; Nagai, Fumio; Fujita, Kenya; Noguchi, Masahiko
Objective: There have been few reports addressing asymmetric bilateral cleft lip repair with contralateral lesser form defects. Two studies have described the thin medial tubercle as the most common remaining labial deformity. In this study, we aimed to evaluate the use of a foxtail-shaped vermilion flap to reconstruct the median tubercle in primary repair. Design: A blinded retrospective study of photography and chart review. Setting: Shinshu University Hospital, tertiary care. Private practice. Patients: Forty-nine patients with asymmetric bilateral cleft lip with lesser form defects treated using a primary "unilateral" repair by the senior author (S.Y.) between 2007 and 2017. Interventions: The foxtail-shaped vermilion flap was applied at the time of the primary nasolabial repair. This flap is similar to Noordhoff laterally based triangular vermilion flap but with modifications to the shape and length. The body of the flap is wider than the pedicle to add tissue to the center of the vermilion, and the length is sufficiently elongated to reach the lesser side. Main Outcome Measure: Lip shape was graded on a 4-point scale when patients were 1 year old. Results: Twenty-two patients were treated with the foxtail-shaped vermilion flap (group A) and 27 patients with Noordhoff triangular vermilion flap (group B). Group A had a better lip shape than group B ( P = .006). Conclusions: The foxtail-shaped vermilion flap is useful to reconstruct the median tubercle in asymmetric bilateral cleft lip repair with contralateral lesser form defects.